Preparation of Functionalized Diorganomagnesium Reagents in Toluene via Bromine or Iodine/Magnesium-Exchange Reactions - Desaintjean, Alexandre; Danton, Fanny; Knochel, Paul (Synthesis, 2021)
A wide range of polyfunctionalized di(hetero)aryl- and dialkenyl-magnesium reagents are prepared in toluene within 10 to 120 minutes between –78 °C and 25 °C via an I/Mg- or Br/Mg-exchange reaction using reagents of the general formula R2Mg (R = sBu, Mes). Highly sensitive functional groups, such as triazene or nitro, are tolerated in these exchange reactions, enabling the synthesis of various functionalized (hetero)arene and alkene derivatives after quenching with several electrophiles including allyl bromides, acyl chlorides, aldehydes, ketones, and aryl iodides.
Keywords: alkenes; apolar solvents; arenes; Grignard reaction; halogen/magnesium-exchange; heterocycles; magnesium